The Role of The Tourism Aware Group in The Economic Development of The Community of Burai Tourism Village - Husin, Azizah; Sari, Meli Permata (Universitas Negeri Semarang, 2023)
This study aims to determine the role of tourism awareness groups in the economic development of the Burai Tourism Village community, Ogan Ilir Regency. This type of research is descriptive qualitative with interview, observation, and documentation methods. The results of the study show that the tourism awareness group in Burai Village has become a partner of the government in tourism development, from the development of tourism that has been carried out the tourism awareness group has been able to provide business opportunities and also employment opportunities for the community. Tourism awareness groups as beneficiaries try to provide positive benefits for the community from the development of tourism, the benefits felt in the form of economic development through the Micro, Small and Medium Enterprises (MSME) sector are marked by the increasing number of requests for goods. The tourism awareness group in creating a conducive environment and atmosphere seeks to provide understanding to the community to be good hosts, in creating a conducive atmosphere the value of Sapta Pesona becomes an inseparable element. The creation of a conducive atmosphere in tourist attractions is able to attract tourists who want to visit so that later it will have a positive influence in the form of increasing the number of requests for goods produced by Micro, Small and Medium Enterprises (MSMEs), creating job opportunities and the community is able to read business opportunities